Quality of Life of Adult Survivors After Extra Corporeal Membrane Oxygenation (ECMO): A Quantitative Study. Issue 1 (January 2018) - Galazzi, Alessandro; Brambilla, Alessandra; Grasselli, Giacomo; Pesenti, Antonio; Fumagalli, Roberto; Lucchini, Alberto
Abstract : Introduction: Extracorporeal Membrane Oxygenation (ECMO) is a technique used in the treatment of patients with severe respiratory failure. A lot of studies in the literature investigated the survival rate of patients treated with ECMO, but few are those that assess the long-term outcomes and the quality of life (QoL) of survivors. Materials and Methods: A retrospective observational study with prospective QoL assessment through administration of the questionnaire EuroQol-5 Dimension was conducted in acute respiratory distress syndrome patients who h ad ECMO as a rescue therapy for reversible refractory hypoxemia from January 2013 until December 2015 in an Italian referral ECMO center. Results: Forty patients were enrolled, but the telephone interview was possible only in 17. The interviewed patients presented a reduction in QoL in the items concerning pain (59%), followed by problems regarding mobility (47%) and anxiety (47%). The patients' perceived QoL, showed in a 0 to100 scale (0 being the worst, 100 being the best value), is of 75% (interquartile range, 70-80). Discussion: The problems found are in agreement with the literature about this particular type of patients. Conclusion: Most ECMO patients have good physical and social functioning after hospital discharge.